MPC1 Deficiency Promotes CRC Liver Metastasis via Facilitating Nuclear Translocation of β-Catenin - Guang-Ang Tian; Chun-Jie Xu; Kai-Xia Zhou; Zhi-Gang Zhang; Jian-Ren Gu; Xue-Li Zhang; Ya-Hui Wang (Journal of Immunology Research)
Accumulating evidence has pointed out that metastasis is the leading cause of death in several malignant tumor, including CRC. During CRC, metastatic capacity is closely correlated with reprogrammed energy metabolism. Mitochondrial Pyruvate Carrier 1 (MPC1), as the carrier of transporting pyruvate into mitochondria, linked the glycolysis and TCA cycle, which would affect the energy production. However, the specific role of MPC1 on tumor metastasis in CRC remains unexplored. Here, by data mining of genes involved in pyruvate metabolism using the TCGA dataset, we found that MPC1 was significantly downregulated in CRC compared to nontumor tissues. Similar MPC1 expression pattern was also found in multiple GEO datasets. IHC staining in both human sample and AOM/DSS induced mouse CRC model revealed significant downregulation of MPC1. What is more, we found that MPC1 expression was gradually decreased in normal tissue, primary CRC, and metastasis CRC. Additionally, poor prognosis emerged in the MPC1 low expression patients, especially in patients with metastasis. Following, functional tests showed that MPC1 overexpression inhibited the motility of CRC cells in vitro and MPC1 silencing enhanced liver metastases in vivo. Furthermore, we uncovered that decreased MPC1 activated the Wnt/β-catenin pathway by promoting nuclear translocation of β-catenin to mediate the expression of MMP7, E-cadherin, Snail1, and myc. Collectively, our data suggest that MPC1 has the potential to be served as a promising biomarker for diagnosis and a therapeutic target in CRC.